The Power behind Empowerment for Staff Nurses: Using Foucault's Concepts - Sonia A. Udod (Nursing Leadership, 2008)
The concept of staff nurse empowerment is often evoked in dialogue concerning the nature of nurses' practice in improving their work environments. Nurse empowerment has been the subject of vigorous discussion in healthcare settings, and has been researched largely through an organizational perspective. In this paper, nurse empowerment is analyzed by drawing upon a critical science approach as an alternative theoretical lens. Power is integral to empowerment, and occurs in the context of relations of power. The author uses the ideas of Michel Foucault to address the different ways in which power relations shape nurses' experiences in the workplace. Foucault conceptualizes power as a form of power that envelops staff nurses and nurse managers and, more specifically, as a set of disciplinary techniques. Rather than discussing power solely as a repressive force, Foucault identifies the productive aspects of power. His analysis of where power resides suggests a thought-provoking approach to staff nurse empowerment that has the potential to change nurses' practice through points of resistance, and thus has implications for improving the quality of nurses' work life.
Keywords: workplace empowerment, nursing leadership, work environment, power relations